Step
*
1
1
of Lemma
es-increasing-sequence
.....assertion..... 
1. es : EO@i'
2. m : ℕ+@i
3. f : ℕm ─→ E@i
4. ∀i:ℕm - 1. (f i <loc f (i + 1))@i
⊢ ∀d:ℕ. ∀i:ℕm. ∀j:ℕi.  (((i - j) ≤ d) 
⇒ (f j <loc f i))
BY
{ InductionOnNat }
1
.....basecase..... 
1. es : EO@i'
2. m : ℕ+@i
3. f : ℕm ─→ E@i
4. ∀i:ℕm - 1. (f i <loc f (i + 1))@i
5. d : ℤ
⊢ ∀i:ℕm. ∀j:ℕi.  (((i - j) ≤ 0) 
⇒ (f j <loc f i))
2
.....upcase..... 
1. es : EO@i'
2. m : ℕ+@i
3. f : ℕm ─→ E@i
4. ∀i:ℕm - 1. (f i <loc f (i + 1))@i
5. d : ℤ
6. 0 < d
7. ∀i:ℕm. ∀j:ℕi.  (((i - j) ≤ (d - 1)) 
⇒ (f j <loc f i))
⊢ ∀i:ℕm. ∀j:ℕi.  (((i - j) ≤ d) 
⇒ (f j <loc f i))
Latex:
.....assertion..... 
1.  es  :  EO@i'
2.  m  :  \mBbbN{}\msupplus{}@i
3.  f  :  \mBbbN{}m  {}\mrightarrow{}  E@i
4.  \mforall{}i:\mBbbN{}m  -  1.  (f  i  <loc  f  (i  +  1))@i
\mvdash{}  \mforall{}d:\mBbbN{}.  \mforall{}i:\mBbbN{}m.  \mforall{}j:\mBbbN{}i.    (((i  -  j)  \mleq{}  d)  {}\mRightarrow{}  (f  j  <loc  f  i))
By
InductionOnNat
Home
Index